2010
DOI: 10.1007/s10433-010-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Five views of a secret: does cognition change during middle adulthood?

Abstract: This study examined five aspects of change (or stability) in cognitive abilities in middle adulthood across a 12-year period. Data come from the Interdisciplinary Study on Adult Development. The sample consisted of N = 346 adults (43.8 years on average, 48.6% female). In total, 11 cognitive tests were administered to assess fluid and crystallized intelligence, memory, and processing speed. In a first series of analyses, strong measurement invariance was established. Subsequently, structural stability, differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 50 publications
(48 reference statements)
2
33
1
Order By: Relevance
“…These studies provide evidence that there are declines in cognitive functioning as early as the mid 40s (Anstey, Sargent-Cox, Garde, Cherbuin, & Butterworth, 2014; Brunner et al, 2017; Davis et al, 2017; Rönnlund & Nilsson, 2006; Singh-Manoux et al, 2012; Zimprich & Mascherek, 2010). Findings on age differences from cross-sectional, normative studies of cognitive batteries such as the Wechsler Adult Intelligence Scale (WAIS; Wechsler, 1997), are consistent with these longitudinal findings (Ryan, Sattler, & Lopez, 2000).…”
Section: Cognitive Agingmentioning
confidence: 96%
“…These studies provide evidence that there are declines in cognitive functioning as early as the mid 40s (Anstey, Sargent-Cox, Garde, Cherbuin, & Butterworth, 2014; Brunner et al, 2017; Davis et al, 2017; Rönnlund & Nilsson, 2006; Singh-Manoux et al, 2012; Zimprich & Mascherek, 2010). Findings on age differences from cross-sectional, normative studies of cognitive batteries such as the Wechsler Adult Intelligence Scale (WAIS; Wechsler, 1997), are consistent with these longitudinal findings (Ryan, Sattler, & Lopez, 2000).…”
Section: Cognitive Agingmentioning
confidence: 96%
“…Schaie (2005) and Zimprich and Marcherek (2010) also reported lower stability coefficients for memory ability than for other cognitive abilities, and therefore episodic memory may be a special case in which individual differences in change are more pronounced than with other abilities, particularly among older adults. The greater variability and lower stability for memory may reflect the presence of some individuals with pre-clinical dementia in the older sample as memory decline is recognized as one of the earliest symptoms of dementia.…”
Section: Discussionmentioning
confidence: 90%
“…For example, Ronnlund, et al (2005) reported 5-year stability coefficients of .80 for an episodic memory factor and .89 for a semantic memory factor. The estimated correlation for a latent construct of fluid intelligence over a 5-year interval was .98 in a study by Raz, et al (2008), and Zimprich and Mascherek (2010) recently reported 12-year stabilities of .95 for a fluid intelligence construct, .93 for a crystallized intelligence construct, .91 for a speed construct, and .58 for a memory construct. Only two reports could be found in which stability coefficients were computed for adults in different age groups, and both suggested little or no age differences in the magnitude of stability.…”
mentioning
confidence: 95%
“…A unique feature of midlife may be that it is the developmental period characterized by the balance of gains and losses. As was illustrated in articles on cognition (Zimprich and Mascherek 2010) and personality (Allemand et al 2010) in this issue, some domains of functioning are still increasing (e.g., vocabulary), many domains are being maintained (i.e., stability in personality), and others are beginning to decline (e.g., speed). This tie in gains and losses in midlife is said to be associated with a balance in the impact of biology and culture.…”
mentioning
confidence: 96%